IMPROVEMENT OF EMPLOYEE PERFORMANCE THROUGH A HIGH LEVEL OF EMPLOYEE DISCIPLINE - Anton Budi Santoso; Shinta Oktafien (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
This study aims to determine to what extent the influence of high work discipline on improving employee performance at PT. BPR Karyajatnika Sadaya (BPR KS). The population in this study is all employees who work in this company, amounting to 60 people with sampling using saturated sampling technique, which means that the number of samples taken is the whole of the population members. The research method used is a descriptiveverification research method. And for the data processing and analysis techniques used, namely in the form of simple regression analysis calculated using statistical tools in the form of the SPSS 20 for Windows software program. Based on the results of data processing and analysis obtained, it is known that high work discipline has a significant effect on improving employee performance. This shows that if employees at work are able to show a high level of work discipline, meaning that employees have a high level of compliance in obeying all applicable work regulations in their company, then these employees can show better work results.